Sensorless second-order switching surface for a three-level boost converter - Messikh, Tarek; Rahim, Nasrudin Abd; Mekhilef, Saad (Turkiye Klinikleri Journal of Medical Sciences, 2019)
This paper proposes a sensorless second-order switching surface to control a three-level boost converter (TLBC). A predictive current method is proposed to reduce the number of sensors in the normal second-order switching surface method. Based on a developed model of the TLBC, the current is estimated and a switching surface is formulated in the state-energy plane. Simulation and hardware tests are carried out to verify the viability and the effectiveness of the proposed control technique. Results obtained show a good performance of the converter in term of DC-bus balancing and fast dynamic response under sudden load change. © TÜBİTAK.